Reading and writing in kindergarten - Franzese, Rosalie (U.S.A : Scholastic, 2002)
Lessons and strategies that help young learners develop literacy skills through shared reading, guided reading, Interactive writing,Read alouds, and more
A practical guide
Keywords: Interactive writing; Shared reading